Mechanisms of muscle growth and atrophy in mammals and Drosophila. Issue 2 (24th October 2013) - Piccirillo, Rosanna; Demontis, Fabio; Perrimon, Norbert; Goldberg, Alfred L.
<x xml:space="preserve">Abstract</x> Background: The loss of skeletal muscle mass (atrophy) that accompanies disuse and systemic diseases is highly debilitating. Although the pathogenesis of this condition has been primarily studied in mammals, Drosophila is emerging as an attractive system to investigate some of the mechanisms involved in muscle growth and atrophy. Results: In this review, we highlight the outstanding unsolved questions that may benefit from a combination of studies in both flies and mammals. In particular, we discuss how different environmental stimuli and signaling pathways influence muscle mass and strength and how a variety of disease states can cause muscle wasting. Conclusions: Studies in Drosophila and mammals should help identify molecular targets for the treatment of muscle wasting in humans. Developmental Dynamics 243:201–215, 2014. © 2013 Wiley Periodicals, Inc.